Correction: Effect of the annealing temperature and of Bi substitution on the structural and magnetic behaviors of double-doping (Bi/La, Ca) (La0.8Ca0.2)1−xBixFeO3 compounds. (6th February 2023) - Issaoui, H.; Benali, A.; Bejar, M.; Dhahri, E.; Santos, R. F.; Costa, B. F. O.
Abstract : Correction for 'Effect of the annealing temperature and of Bi substitution on the structural and magnetic behaviors of double-doping (Bi/La, Ca) (La0.8 Ca0.2 )1− x Bi x FeO3 compounds' by H. Issaoui et al., New J. Chem., 2020, 44, 9813–9821, ; https://doi.org/10.1039/D0NJ01962C .